2018
DOI: 10.2147/idr.s189494
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and molecular characterization of multidrug-resistant <em>Klebsiella pneumoniae</em> isolates harboring <em>bla</em><sub>CTX-M-15</sub> extended-spectrum &beta;-lactamases causing ventilator-associated pneumonia in China

Abstract: BackgroundVentilator-associated pneumonia (VAP) is a common nosocomial infection associated with high morbidity due to multidrug-resistant (MDR) pathogens. The purpose of this study was to determine the occurrence of extended-spectrum β-lactamase (ESBL) genes, especially blaCTX-M-15, in Klebsiella pneumoniae (K. pneumoniae)-associated VAP and to investigate the antimicrobial resistance patterns and molecular epidemiological characteristics of K. pneumoniae strains.Materials and methodsFrom January 2013 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(42 reference statements)
2
11
0
Order By: Relevance
“…In addition, multiresistant strains increase the risk of infections caused by treatment failure in humans and animals. Multiresistant K. pneumonia isolates have emerged in many countries, including Northwest Iran, Turkey, Australia and China 25–28. Our study also showed a high occurrence of multiresistant K. pneumonia among humans and different animals, which suggest that these multiresistant strains can potentially be transmitted among humans and animals.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, multiresistant strains increase the risk of infections caused by treatment failure in humans and animals. Multiresistant K. pneumonia isolates have emerged in many countries, including Northwest Iran, Turkey, Australia and China 25–28. Our study also showed a high occurrence of multiresistant K. pneumonia among humans and different animals, which suggest that these multiresistant strains can potentially be transmitted among humans and animals.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, isolate 1TR5R was susceptible to tobramycin, ceftazidime, and minocycline. Multidrug resistant K. pneumoniae has been reported by previous researchers [32,33], and is globally spreading unabated. This might lead to increased hospital stay and K. pneumoniae associated mortality.…”
Section: Antibiogram Of Colistin Resistant K Pneumoniae Isolatesmentioning
confidence: 91%
“…Of note, we observed some known epidemic clones among the E. coli (i.e., ST10 and ST38) and K. pneumoniae (i.e., ST15 and ST307) isolates ( Woodford et al, 2011 ; Mathers et al, 2015 ; Navon-Venezia et al, 2017 ). K. pneumoniae ST15 isolates harboring bla CTX–M –15 , are emerging among patients with respiratory tract infections in China ( An et al, 2012 ; Xu et al, 2019 ) and have been previously isolated from companion animals in Paris ( Morcatti et al, 2018 ). As previously described, our data reveal clonal diversity among the recovered isolates and highlight Brazilian poultry meat as a reservoir of ExPEC lineages (i.e., ST10) ( Casella et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%